Intrapersonal and Interpersonal Functions as Pathways to Future Self-Harm Repetition and Suicide Attempts - Gardner, Kathryn Jane; Paul, Elise; Selby, Edward A.; Klonsky, E. David; Mars, Becky (Frontiers in Psychology, 2021)
Background: Research has identified functions of non-suicidal self-harm/self-injury (NSSH) but whether functions change over time, from adolescence to early adulthood, or predict the continuation of the behaviour prospectively remains unclear. This study aimed to prospectively explore whether intrapersonal and interpersonal NSSH functions in adolescence predict repetition of self-harm (regardless of suicidal intent) and incident suicide attempts in early adulthood. Methods: Participants were 528 individuals with NSSH at age 16 years from the Avon Longitudinal Study of Parents and Children (ALSPAC), a population-based birth cohort in the UK. Descriptive statistics were used to explore changes in functions over time from age 16 to 21, and logistic regression used to examine associations between NSSH functions and repeat self-harm and suicide attempts at age 21, 24 and 25 years. Findings: The majority of 16-year-olds with NSSH endorsed intrapersonal (e.g., affect regulatory) functions only (73% at 16 years and 64% at 21 years). Just under half of adolescents (42%) and three quarters of 21 years olds reported more than one function simultaneously. A greater number of intrapersonal functions at 16 years independently predicted future repetition of self-harm at ages 21-25 years, over and above interpersonal functions (OR=1.46, 95% CI 1.06 to 2.01). Interpersonal functions during adolescence did not predict repeat self-harm or suicide attempts in adulthood. Discussion: Our findings suggest that intrapersonal but not interpersonal NSSH functions are a prospective risk factor for future self-harm and might also predict incident suicide attempts. The results highlight the central role of underlying affective difficulties and motivations in self-harm maintenance.